Attitudes and Perceptions of Patients on the Kidney Transplant Waiting List toward Mobile Health—Delivered Physical Activity Programs. (March 2015) - Sieverdes, John C.; Raynor, Phyllis A.; Armstrong, Tracy; Jenkins, Carolyn H.; Sox, Luke R.; Treiber, Frank A.
Context: Dialysis patients' lifestyles are associated with low levels of physical activity, increasing the chances of being removed from kidney waiting lists or dying while awaiting transplant because of increased cardiovascular risk factors and deteriorating health conditions. Personalized mobile health (mHealth) delivered programs may support their engagement in healthier lifestyles, maintain transplant eligibility, and reduce premature mortality. Objective: To explore barriers and perceptions of physical activity behaviors and gauge interest in using mHealth in a physical activity wellness program for dialysis patients on the kidney transplant waiting list. Participants and Design: In-depth key informant interviews were conducted with 22 randomly selected dialysis patients during dialysis treatment in an urban Southeastern coastal city. A theory-guided community-based participatory research approach was used to develop the interview content. Constructivist grounded theory guided the data analysis using NVIVO 10 (QSR Int). The 32-item checklist from the Consolidated Criteria for Reporting Qualitative Studies was used in the qualitative reporting. Results: Dialysis patients had a mean age of 46 (SD, 10.7) years, 45% were female, and 82% were African American. Their mean duration on transplant waiting lists was 6.7 (SD 4.3) years, and 73% owned smartphones. After saturation was reached, predominant themes included (1) physical activity was perceived as optional, (2) social support both encouraged and limited physical activity, (3) chronic stress and coping influenced physical activity, (4) spirituality provided strength to engage in physical activity, (5) self-care management practices varied considerably, and (6) high interest (95%) for using mHealth to promote physical activity was found. Patients preferred their home and neighborhood environments to intradialytic settings for engaging in physical activity.